Determinant Analysis of Labor Absorption in the Agricultural Sector in South Sulawesi Province (1999 - 2019) - Andi Arlianti Dwiputri; Fatmawati Fatmawati; Sultan Suhab (Jambura Equilibrium Journal, 2023)
This study aims to examine and analyze the direct and indirect effects of investment in the agricultural sector, regional capital expenditures for the agricultural sector, the Provincial Minimum Wage (UMP) on the absorption of labor in the agricultural sector in South Sulawesi Province through the Gross Regional Domestic Product (GRDP) ) the agricultural sector and the Human Development Index (IPM). The data used in this study is secondary data from the Central Bureau of Statistics (BPS) in the form of a time series from 1999 to 2019. In this study using the structural equation regression analysis method using SPSS software . The analysis technique used in this study is Path Analysis. The results of the study show that investment in the agricultural sector has an effect both directly and indirectly on the employment of the agricultural sector in South Sulawesi Province through the agricultural sector's Gross Regional Domestic Product (GRDP). Regional capital expenditures for the agricultural sector influence both directly and indirectly the absorption of labor in the agricultural sector in South Sulawesi Province through the agricultural sector's Gross Regional Domestic Product (GRDP) and the Human Development Index (IPM). The Provincial Minimum Wage (UMP) has no direct or indirect effect on employment in the agricultural sector in South Sulawesi Province through the agricultural sector's Gross Regional Domestic Product (GRDP) and the Human Development Index (IPM).